Pelatihan Literasi Digital Pada Gerakan Pramuka SMAN 1 Campalagian - Irianti, Arnita; Rasjid, Nurdina; Rustan, Muh. Fahmi (Journal Of Computer Science Contributions (JUCOSCO), 2022)
Community Service Activities (PKM) were carried out by the Lecturer Team of the University of West Sulawesi Informatics with the aim of educating students of SMAN 1 Campalagian about digital literacy. This PKM activity is packed with the theme of smart generation in digital literacy. Digital literacy activities contain the provision of knowledge regarding the introduction of digital literacy, social media ethics and the Information Law and the ITE Law. In addition, there is also a provision in the field of skills by using a poster-making application, namely Canva. Posters are made with the theme of education about digital literacy. The method used in this PKM is lectures and discussions for knowledge of digital literacy concepts. While poster training with lectures, discussions and hands-on practice of making educational posters. This PKM activity is expected to play an active role in the socialization of digital literacy at SMA Negeri 1 Campalagian. Digital literacy education at SMAN 1 Campalagian began in the scouting movement to form noble character/personality and morals for the younger generation in the field of digital literacy. With this workshop, it is hoped that members of the scout movement can become the driving force in the digital literacy movement at SMAN 1 Campalagian. The target achievement in this training is that participants are able to explain the basic concepts of digital literacy and create digital literacy education posters. Participants were very enthusiastic in this Digital Literacy Activity as seen in the discussion between the presenters and participants. There is an exchange of information and experiences between participants and speakers involved in digital literacy. This is to maximize the positive impact of the development of information in terms of the ability to review and select the right information. And minimize the negative impact in facing the challenges of the digital world.